(untitled) (Medical Forum Monthly, 2024)
Objective: A study was conducted to investigate features of death due to strangulation in Lahore and to compare them with other studies on this subject. Materials and methods: 220 cases of strangulation were selected out of 2979 total medico legal autopsies conducted at Forensic Medicine department K.E.M.U Lahore during Jan, 2006-Dec,2008.The selected cases were analyzed for different variables. Results: Neck compression constituted 7.39% of total autopsies and 89.43% of total asphyxial deaths. Hanging accounted for 42.27% followed by ligature strangulation 29.09% and throttling 23.64%. All types of strangulation were prevalent in 2nd, 3rd & 4th decade of life. No case was noticed in age below 1 year. No hanging was noticed in 1st decade of life. Male had higher incidence over females in hanging in 3rd and 4th decade. Female had higher incidence in 2nd 3rd and 4th decade in ligature strangulation. Male had higher incidence in 3rd and female in 4th decade in throttling. Homicidal deaths accounted for 57.27%, suicidal 30.90%and undeterminable for 11.82%. Ligature strangulation and throttling were the methods used for homicide 57.27% while hanging was used for suicide 30.97%. Above the thyroid cartilage, the marks were 58.63% with M/F ratio 1.86:1 giving. 53 (41.08%) fractures of the hyoid bone while marks at thyroid cartilage were 36.81% with M/F 1.79:1 giving (3) 3.70% hyoid bone fractures. Below thyroid cartilage 4.5% marks showed no hyoid bone fractures. Throttling showed hyoid bone fracture 69.23%, hanging 14.42%& ligature strangulation 7.81%. Ligature material used was soft in 47.62% cases and hard in 40.48%. It was used in single whirl in 57.41% cases and in multiple whirls in 42.86% cases. Ill defined marks were 40.45% and well defined were 64.09%. In hanging knot was present on occiput in 62.50% cases and on lateral sides in 23.08% cases while 78.13%cases showed the knot on front and 21.87% cases on lateral side in ligature strangulation. Congestion was found in 85.45%, petechial hemorrhage in 81.81% and cyanosis in 75.54% cases. Conclusion: Asphyxial death due to strangulation is common in our country in young age group in males. Hanging is a common method of suicide while ligature strangulation& throttling are used for homicide. The presence of compressive marks above thyroid cartilage are suggestive of death due to hanging and throttling while their presence at and below thyroid cartilage indicate ligature strangulation. This compressive trauma may or may not be associated with fracture of hyoid bone , which is a strong evidence of death due to strangulation.